FUNCTIONS OF OLYMPIC EDUCATION IN CONTEMPORARY SCHOOL - Boyanka Peneva (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
Contemporary circumstances make specialists to connect the conception of Olympic education not only with the Olympic movement as an imposing social phenomenon but with school education on all levels as well. Nowadays two orientations are outlined: 1) Researches to Olympism 2) Teaching through Olympism First direction of Olympic education is turned to the enrichment of the researches about Olympism in the different countries and spread the gathered new knowledge all around the earth. This direction concerns enrichment of the academic programmes. Second direction is connected with young generation (pupils, students and athletes) and youth programmes and projects, based on the Olympic principles. This paper is a study on the problem starting from the renewal of the contemporary Olympic Games in 1896 to nowadays and the Beijing Olympic Games in 2008. Olympic education concerns not only the content of the lessons of physical education but the other school subjects as well. This is a new world's tendency.